Enkapsulasi Kurkumin dalam Matriks Beads Kitosan-Karaginan yang Tertaut-Silang dengan Glutaraldehida menggunakan Asam Laurat sebagai Pengemulsi - Zhilal Shadiq; Muhamad Sofi Ardani; Nur Indah Wardani; Annisa Yuliana Angeline; Sari Sekar Ningrum (Universitas Hamzanwadi, 2025)
Curcumin (diferuloylmethane), the primary bioactive compound in turmeric (Curcuma longa), is a natural polyphenol with proven pharmacological properties. Its safety and biodegradability, along with multifunctional health benefits, have been well-documented. However, curcumin exhibits poor water solubility. Consequently, curcumin shows low systemic bioavailability and rapid urinary excretion. A carrier matrix is essential to improve bioavailability and prolong systemic retention of curcumin, and one of carrier matrix that can be utilized is a bead matrix. In this study, bead matrices were prepared by combining a chitosan solution with lauric acid and carrageenan solutions and then dropping the mixture into a sodium hydroxide solution, which acts as an ionic neutralizing agent during bead formation. The encapsulation process was conducted by immersing the formed bead matrices in curcumin and glutaraldehyde solutions to facilitate crosslinking reactions with chitosan. The resulting bead matrices were analyzed using FT-IR spectroscopy to determine the interactions and bonds formed between the materials used. The results indicated that the encapsulation efficiency of curcumin was influenced by the concentrations of chitosan and lauric acid, with higher concentrations of both components leading to increased encapsulation efficiency.